Breakfast consumption habit and its impact on nutrient intake and nutritional status of medical undergraduates - Mathiyalagen, Prakash; Yadav, Dhananjay; R, Anandaraj; Vasudevan, Kavita; Sundar, Buvaneshwari; R, Priyadharsini; Mishra, Meerambika; Jin, Jun-O (Progress in Nutrition, 2019)
Aim: Breakfast is considered the most important meal of the day, the quality and quantity of which potentially contributes to the total daily energy and nutritional well-being of an individual. Gluttony, sedentary lifestyle and obesity are common among the breakfast skippers. Among numerous lifestyle factors contributing to overweight in youth, skipping breakfast has been identified as a potential risk factor but with controversial results.  Hence, this study was aimed to investigate the impact of breakfast skipping habit among the undergraduate students with nutrient intake and nutritional status. Material and methods: This cross-sectional study was conducted among undergraduates studying in a medical college of Puducherry. 274 students who agreed to participate filled a pre-tested semi-structured questionnaire having a dietary record over 3 consecutive days including Sunday. Standard WHO (World Health Organization) techniques and guidelines for anthropometric measurements and BMI classification and ICMR (Indian Council of Medical Research) dietary guidelines to calculate calorific values of food items was used. Chi-square test, Student’s t test and Mann-Whitney U test was used and p value